Monetary Policy and Intangible Investment - Dottling, Robin (IMF Working Papers; Working Paper ;, 2020)
We contrast how monetary policy affects intangible relative to tangible investment. We document that the stock prices of firms with more intangible assets react less to monetary policy shocks, as identified from Fed Funds futures movements around FOMC announcements. Consistent with the stock price results, instrumental variable local projections confirm that the total investment in firms with more intangible assets responds less to monetary policy, and that intangible investment responds less to monetary policy compared to tangible investment. We identify two mechanisms behind these results. First, firms with intangible assets use less collateral, and therefore respond less to the credit channel of monetary policy. Second, intangible assets have higher depreciation rates, so interest rate changes affect their user cost of capital relatively less.